0VIP0SITION PREFERENCE OF SCJRPOPHAGA INCERTULAS (WALKER) ON DIFFERENT VARIETIES OF RICE UNDER CAGED CONDITION (Biological Sciences - PJSIR, 2002)
Preference of Yellow Stem Borer (YSB) female for egg deposition on 21 aus and 11 arnan  rice  varieties  were  observed under caged conditions during 1992, 1993 and 1994. Significant differences in the number of egg mass  deposition  on  different rice va1ieties were found excepti ng on aus, 1992 and aman, 1994. The dorsal side ofleaf was preferred to ventral  side for egg deposition irrespective of the rice variety . Again , the middle portion of  leaf was  preferred  for egg laying  to basal and apical portions in all the varieties . Length and width of egg masses deposited on different rice varieties did not  differ significantly except the length  of the egg mass  in  aus season. The number  of egg masses deposited  by the female  YSB was positively correlated with leaf blade colour but negatively correlated with  plant  height,  2nd  leaf  length  and  width , number of leaves, number of tillers and leaf hair in both aus and aman rice. So, the leaf blade colour induces egg deposition , while  other  plant  characters  reduce it.